2022
DOI: 10.3390/cells11030534
|View full text |Cite
|
Sign up to set email alerts
|

Valproic Acid-Induced CCN1 Promotes Osteogenic Differentiation by Increasing CCN1 Protein Stability through HDAC1 Inhibition in Tonsil-Derived Mesenchymal Stem Cells

Abstract: Our previous study found that the level of CCN1 increases as osteogenic differentiation progresses in tonsil-derived mesenchymal stem cells (TMSCs). This study investigated how CCN1 is regulated through HDAC inhibition in TMSCs and their relationship with osteogenesis. Valproic acid (VPA) (1–5 mM), a well-known histone deacetylase (HDAC) inhibitor, strongly inhibited TMSC proliferation without altering MSC-specific surface markers, CD14, 34, 45, 73, 90 and 105. However, CD146 expression increased at 5 mM VPA. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…CCN1, LAPTM5, and ArhGAP15 are among the most common genes. CCN1 is linked to HDAC1 inhibition 40 , and LAPTM5 has been identified as an mRNA signature for PTCL 41 . For ArhGAP15, one of its gene family, ArhGAP30, is associated with histone acetylation, which is known to facilitate p53 acetylation 42 .…”
Section: Resultsmentioning
confidence: 99%
“…CCN1, LAPTM5, and ArhGAP15 are among the most common genes. CCN1 is linked to HDAC1 inhibition 40 , and LAPTM5 has been identified as an mRNA signature for PTCL 41 . For ArhGAP15, one of its gene family, ArhGAP30, is associated with histone acetylation, which is known to facilitate p53 acetylation 42 .…”
Section: Resultsmentioning
confidence: 99%
“…Other groups were reported that adipose tissue-derived stem cells could also differentiate into neuronal cells by treating VPA [ 12 , 49 ]. Similarly, it has been reported that VPA has a potential as an agent of neurogenic differentiation via activating histone H3 core acetylation in embryonic stem cells [ 50 ] and osteogenic differentiation in tonsil-derived mesenchymal stem cells [ 51 ]. Animal studies have also shown that VPA treatment in the rat cerebral cortex induced differentiation via activation of the ERK-P21 Cip/WAFI pathway [ 45 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, HDAC1 and HDAC2 silencing and overexpression were reported to regulate osteogenesis in cell types other than MSCs; however, one has a positive effect 48,49 which means they enhance osteogenesis, whereas the other shows negative effects 47,50 which means they regulate the expression of the osteogenic gene osteocalcin or the osteoclastogenic gene RANKL. Therefore, these results should be considered characteristic effects of hBM‐MSCs interacting with periodontal cells, HPL cells, and HGFs, and studied further.…”
Section: Discussionmentioning
confidence: 99%